The Influence of the LAZISNU Jombang NU-Care Program on Improving Quality of Life: Phenomenological Study - hendra Pratama; Dian Purnama (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2020)
This research aims to explore the influence of the NU-Care LAZISNU Jombang program on improving the quality of life of beneficiaries, using a qualitative phenomenological approach. Through in-depth interviews and participant observation, this research explores the subjective experiences of beneficiaries in economic, educational, health and social welfare aspects. The research results show that LAZISNU Jombang's NU-Care programs have succeeded in increasing the income and economic stability of beneficiaries, providing better access to education, improving health, and strengthening self-confidence and involvement in community activities. Active participation in community activities increases significantly, which contributes to better psychological and social well-being. This research emphasizes the importance of a holistic approach in empowerment programs that does not only focus on material assistance but also on social empowerment and community participation. It is hoped that these findings can provide broader insight for the development of community empowerment programs in the future